Exchange-correlation energy of a hole gas including valence band coupling - Bobbert, Peter A.; Wieldraaijer, H.; Weide, Rommie Y. van der; Kemerink, Martijn; Koenraad, Paulus M.; Wolter, Joachim H. (Physical review. B, Condensed matter and materials physics, 1997)
We have calculated an accurate exchange-correlation energy of a hole gas, including the complexities related to the valence band coupling as occurring in semiconductors like GaAs, but excluding the band warping. A parametrization for the dependence on the density and the ratio between light- and heavy-hole masses is given. We apply our results to a hole gas in an AlxGa1−xAs/GaAs/AlxGa1−xAs quantum well and calculate the two-dimensional band structure and the band-gap renormalization. The inclusion of the valence band coupling in the calculation of the exchange-correlation potentials for holes and electrons leads to a much better agreement between theoretical and experimental data than when it is omitted.